Effect of different depth on fish catches in Hajoran Coast of Central Tapanuli District: Case on bamboo platform lift net. Issue 1 (February 2021) - Iqbal, T H; Sitompul, D P; Rianjuanda, D; Miswar, E; Salmarika,; Aprilla, R M
Abstract: Central Tapanuli Regency is one of the regions in North Sumatra that has fishery potential. In Hajoran, the livelihoods of most people as fishermen are on bamboo platform lift net fishing gear. Bamboo platform lift net is a fishing gear that catches small pelagic fish and is installed permanently. The factor of the installation of a bamboo platform lift net at a different depth will affect the income earned by each fisherman. The purpose of this study was to compare the catches of fish that were predominantly caught on a bamboo platform lift net based on different depths. This research was conducted in February 2020 at Hajoran Village, Central Tapanuli regency in Sibolga City, by using a survey method. Data collection was carried out by directly recording the catches 3 units of bamboo platform lift net and then comparing the three results by using One Way ANOVA analysis. The results showed that the amount of catch per lift net varies, depending on the type of fish and its depth. For pony fishes, species were more commonly found at a depth of 30 M with a total of 5.5 kg, while fringescale sardine and anchovies were found at a depth of 36 M with a total of 10.6 kg and 64.4 kg, respectively. One Way ANOVA revealed that there was a significant difference found on fringescale sardine and ponyfish in term of water depth (p < 0.05), while there was no any significant different on anchovy fish (p < 0.05).